2022
DOI: 10.1128/mbio.03702-21
|View full text |Cite
|
Sign up to set email alerts
|

Nanopore-Based Detection of Viral RNA Modifications

Abstract: The chemical modification of ribonucleotides plays an integral role in the biology of diverse viruses and their eukaryotic host cells. Mapping the precise identity, location, and abundance of modified ribonucleotides remains a key goal of many studies aimed at characterizing the function and importance of a given modification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 126 publications
0
27
0
Order By: Relevance
“…In addition, nanopore DRS has been used to detect RNA modifications [20][21][22] . The general schemes are illustrated in Fig.…”
Section: Rna Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, nanopore DRS has been used to detect RNA modifications [20][21][22] . The general schemes are illustrated in Fig.…”
Section: Rna Modificationsmentioning
confidence: 99%
“…2e). These tools are summarized in two recent reviews 20,21 . Most use Nanopolish to these events are then calculated and used to model Gaussian distributions for downstream analysis.…”
Section: Rna Modificationsmentioning
confidence: 99%
“…To capture and retain the native information of total cellular RNAs, the poly(mA) tail added to the 3' end of RNA must be distinguishable from the native poly(A) tail on nanopore. It has been demonstrated that nanopore is sensitive to nucleotide modifications including 2′-OMeA modification [13,21,22]. Therefore, we reasoned that the poly(mA) would generate current traces distinct from the native poly(A) signal on nanopore.…”
Section: The Ionic Current Traces Of the Poly(ma) Tail On Nanopore Ca...mentioning
confidence: 99%
“…The MinION sequencing platform is a compact and lightweight device that weighs only 90 g and can be easily operated by connecting it to computers and other instruments. Its compact size also means that it takes up minimal floor space, measuring no more than 1 m × 1 m × 2 m. [ 32 ] This makes it an invaluable tool for researchers to look to conduct experiments under extreme conditions that would have been impossible to complete on‐site in the past. Moreover, it solves the challenges encountered when transporting biological materials is limited by physical conditions.…”
Section: Nanopore Sequencing Technologymentioning
confidence: 99%